Human Papillomavirus Testing and Disease Recurrence of Cervical Cancer - Soheila Aminimoghaddam; Noor al Sadat Sajedi (Research in Molecular Medicine)
Background: Cervical cancer stands out as one of the most prevalent gynecological cancers. Cervical cancer’s link to human papillomavirus (HPV) testing and recurrence is unclear despite previous studies. Investigating this relationship in Iranian patients is a pivotal aspect of this research. Methods: This study encompassed all cervical cancer patients referred to Firoozgar Hospital, Tehran, Iran, between 2016 and 2018. Utilizing a census method, the patients’ data, including their demographics and treatment details, were extracted from records. Follow-up samples were collected after vaginal cuff or cervix treatment (surgical or radiotherapy). A total of 124 patients were included in the study and categorized into two groups: Patients with recurrence and those without. INNO-LiPA standard test was employed to detect HPV presence. Comparative analysis of various variables, such as age at diagnosis, smoking history, multiple partners, sexually transmitted diseases history, body mass index, abnormal cervix, vaginal fornix involvement, cervical parameters involvement, tumor size, The International Federation of Gynaecology and Obstetrics (FIGO) staging, MRI staging, pathology, and treatment, was conducted between the recurrence and non-recurrence groups. Results: A total of 124 patients were included in the study, with an average age of 45.95±7.45 years. Most patients had an 18-25 kg/m2 body mass index. Based on MRI findings, the most common stage of cervical cancer was stage III, IIB. Squamous cell carcinoma pathology was the most prevalent, observed in 47 patients (37.9%). The most frequently performed treatment modality was radical trachelectomy and adjuvant chemoradiotherapy, accounting for 20 cases (16.1%). There were no significant differences in terms of age at disease diagnosis, smoking history, body mass index, histological type, and treatment type between patients with recurrent disease and those without recurrence. However, a significant difference was observed in terms of lymph node involvement. In addition, the HPV test was positive in 3 cases (2.4%) with recurrence and 11(8.9%) without. These results suggest no relationship between hrHPV (high-risk human papillomavirus) status and disease recurrence (P=0.196). Conclusion: The result of our study showed no correlation between positive HPV test and cervical cancer recurrence. Consequently, HPV testing is not suitable as a reliable predictor for the recurrence of cervical cancer.